Hormonal and ultrasonographic characterization of the seasonal reproductive cycle of male and female Crotalus durissus terrificus - Matayoshi, Priscilla M. [UNESP]; Souza, Priscilla M.; Gasparotto, Vinícius P.O. [UNESP]; Araujo, Michelle S. [UNESP]; Simões, Carla R.B. [UNESP]; Souza, Fabiana F. [UNESP]; Oba, Eunice [UNESP]; Machado, Vânia M.V. [UNESP]; Júnior, Rui S.F. [UNESP]; Prestes, Nereu C. [UNESP] (Colegio Brasileiro de Reproducao Animal - CBRA, 2018)
Research concerning to characterize seasonal reproductive cycle in males and females of Crotalus durissus terrificus by ultrasound and hormonal measurement. Reproductive aspects (follicular and testicular cycles, and pregnancy) from 28 adult snakes (14 males and 14 females) during different months of the years were studied. Snakes housed individually in cages in an environment with controlled luminosity and humidity, and fed monthly. Females were examined by ultrasound during quiescence and active follicular phase, and pregnancy for follicular and embryo/fetal development. Males were evaluated to testicular echotexture and measurements during reproductive and non-reproductive season. The blood samples were collected from males and females for serum testosterone and progesterone determination, respectively. In 77% males the testes were identified by ultrasound and found increased size during summer, decreased serum testosterone in winter, and positive correlation between serum testosterone and testes size. There was no change in testicular echotexture in according to season. Testosterone concentration was decreased during winter and it was positively correlated with testes size. In 71% females, were observed follicular development (vitellogenesis) and gestation since winter to spring by ultrasonography. Parturition occurred mainly in summer. Pregnancy length was 123.0 ± 11.4 days, with mean 6.9 ± 1.5 newborns/female, and there was gradual increase of serum progesterone during this period. There was no variation in progesterone concentration in non-gravid females. Males and females Tropical Rattlesnake show seasonal variation of reproductive cycle and was clear a biennial cycle in female. The ultrasonography can be considered an essential tool to accomplish the follicular development, pregnancy and testicular alterations in Tropical Rattlesnake.
Keywords: Follicle; Gestation; Progesterone; Rattlesnake; Testosterone